Spillover Asymmetry and Why It Matters - Knott, Anne Marie; Posen, Hart E.; Wu, Brian (Management Science, 2009)
Although spillovers are a crucial factor in determining the optimal environment for innovation, there is no consensus regarding their impact on firm behavior. One reason for this may be that models differ in their assumptions for the functional form of the spillover pool. In industrial organization and economic geography, for example, the predominant convention is that all innovation within an industry/region contributes to a spillover pool that has a common value for all firms. An alternative convention prevalent in endogenous growth and evolutionary economics is that spillovers have directionality—the size of the relevant pool differs across firms. Knowing the correct functional form may facilitate theoretical consensus, either analytically (by modifying models' assumptions) or empirically (by supporting a critical test of competing theories). We characterize and test the functional form of spillover pools for efficiency-enhancing innovation across 50 markets in the banking industry. Our results in that setting are consistent with expectations for asymmetric spillovers but inconsistent with expectations for pooled spillovers.